2019
DOI: 10.1016/j.jtcme.2018.02.002
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of topical application of standardized extract of Tragopogon graminifolius in the healing process of experimental burn wounds

Abstract: Tragopogon graminifolius DC. is a perennial plant from the family Asteraceae which grows in West parts of Iran. Several biological activities like antimicrobial, antioxidant and anti-inflammatory effects are reported for the plant. The aim of this study was to assess the wound healing activity of standardized extract from T. graminifolius (TG) aerial parts. Topical standardized TG extract with 5% and 10% concentrations in eucerine base was assessed for its healing properties on second degree burn in rats durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Among these, the applications of plant based nanotechnology plays a significant role in the process of wound healing [16,17]. The plant based materials have proved at all times to be a powerful remedy for health care [18][19][20][21][22][23][24][25][26][27]. Accordingly, the grape seed extract containing PCs have been investigated for wound treatment and in the management of many illnesses such as cancers, cardiovascular disease, gastric ulcers, obesity and skin inflammations.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the applications of plant based nanotechnology plays a significant role in the process of wound healing [16,17]. The plant based materials have proved at all times to be a powerful remedy for health care [18][19][20][21][22][23][24][25][26][27]. Accordingly, the grape seed extract containing PCs have been investigated for wound treatment and in the management of many illnesses such as cancers, cardiovascular disease, gastric ulcers, obesity and skin inflammations.…”
Section: Introductionmentioning
confidence: 99%
“…54 The pathophysiological activity of Lobelia alsinoides on wound healing in humans and rats using plant extract mediated treatments has been compared with the various preclinical and controlled, randomized and blinded clinical trials previously reported. [55][56][57][58][59][60][61][62][63][64][65][66][67] Though there is no literature reporting on the healing properties patients. 64,72 There are some limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological activity of Lobelia alsinoides on wound healing in humans and rats using plant extract mediated treatments has been compared with the various preclinical and controlled, randomized and blinded clinical trials previously reported 55‐67 …”
Section: Discussionmentioning
confidence: 99%
“…20 A 2 × 2 cm area of skin was excised from the epidermal layer to the subcutaneous layer as well as the connective tissue below it. Wound healing rate was calculated according to Heidari et al.. 21 This study followed the standard of ethics of Health Law research number 23/1992 and obtained ethical approval number 1175/H25.1.11/KE/2017 from the Faculty of Medicine, University of Jember.…”
Section: Methodsmentioning
confidence: 99%